Tree Vegetation Diversity In The Natural Reserve Of Jagat Mountain Sumedang - Sri Wilujeng; Raizal Fahmi Solihat; Reni Anggraini (Green Publisher, 2024)
Mount Jagat is a 133.64-hectare nature reserve area that is directly adjacent to the village and community agricultural land. The designation and management of nature reserves aim to conserve biodiversity, prevent species extinction, protect the forest as a life-support system, and sustainably utilize biodiversity. The threats posed by anthropogenic activities in the Mount Jagat area indicate the need for an inventory and analysis of species diversity, especially tree vegetation, as a first step for conservation. Data collection was carried out using nested quadrats which were placed systematically based on the Land Mapping Unit (LMU). The quadrats were 20 m x 20 m for trees, 10 m x 10 m for poles, 5 m x 5 m for saplings, and 2 m x 2 m for seedlings. The data were then analyzed using Family Importance Value (FIV), Importance Value Index (IVI), Shannon's Diversity Index (H'), and global conservation status by the International Union for Conservation of Nature (IUCN). There are 78 species from 32 families found in the study area. The results showed that the highest FIV for trees was the Moraceae family, 15.43%. The highest FIV for polishes and saplings were in the family Euphorbiaceae with 20.65% and 23.60% respectively. The highest FIV at the seedlings level was the Lauraceae family at 28.47%. Two species were found that had IVI above 10% in almost every growth stage, namely Machilus rimosa (Blume) Blume. and Orophea hexandra Blume. Machilus rimosa (Blume) Blume. found at the tree, pole, sapling, and seedling levels. Orophea hexandra Blume. found at the pole, sapling, and seedling levels. The H' values for the stages of tree growth, polishing, sapling, and seedling were 1.71, 1.63, 1.47, and 1.39, respectively, included in the moderate diversity category. Globally, there are 2 species categorized as vulnerable (VU) and 1 species near threatened (NT) based on IUCN data.